The Role of Brand Awareness in Mediating the Effect of Social Media Marketing on Purchase Intention: A Study on Prospective Consumers of Fore Coffee in Denpasar City - Dewa Kade Anggie Dharma Putra; Ni Ketut Seminari (Digital Innovation : International Journal of Management, 2025)
The growing coffee production rate in Indonesia reflects an increasing public interest in coffee consumption. Fore Coffee, a local coffee shop, has taken advantage of this trend since 2018. However, strong competition from other coffee shops has placed Fore Coffee in third place in the Top Brand Award rankings for the past two years, indicating the need for more effective marketing strategies to boost purchase intention among potential consumers. This study aims to analyze the role of brand awareness in mediating the effect of social media marketing on purchase intention among prospective consumers of Fore Coffee in Denpasar City. The research was conducted with a sample of 120 respondents, using surveys with offline and online questionnaires. The sample was selected through a non-probability purposive sampling method. The data analysis was performed using path analysis and the Sobel test with SPSS version 25. The study’s results indicate that all hypotheses are supported. Social media marketing positively and significantly affects purchase intention, suggesting that effective social media strategies can directly influence consumers' willingness to purchase. Additionally, social media marketing positively impacts brand awareness, meaning that well-executed social media campaigns help consumers become more familiar with the brand. Furthermore, brand awareness has a significant positive effect on purchase intention, implying that increased awareness of Fore Coffee enhances the likelihood of purchase. The study also found that brand awareness partially mediates the relationship between social media marketing and purchase intention, indicating that social media marketing's impact on purchase intention is stronger when combined with high brand awareness. These findings emphasize the importance of integrating social media marketing with brand awareness strategies to improve consumer purchase intention.